Scout Extracurricular Curriculum Management in Improving Student Discipline in Madrasah - Bayu Astra, Nurcholis Panji; Hafid, Erwin; Suban, Alwan (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2024)
The phenomenon of a learning crisis occurred after the COVID-19 pandemic; discipline is one aspect that must be the main focus of schools during this learning crisis. At MTs Arifah, discipline is the primary goal of extracurricular scouting. This study aims to reveal curriculum management in improving student discipline in the scout extracurricular activities. This research also uses a descriptive qualitative approach to tell the facts of curriculum management of the scout extracurricular to improve student discipline. The results obtained from this study reveal that the management of scout extracurricular curriculum planning begins with preparing Prota and Promes as a reference for activities for one year and evaluations carried out by implicit means, namely oral reports by scout coaches to the principal; this evaluation is more effective because the principal is faster and understands the conditions of extracurricular scouting.